Dampak Kebiasaan Mengonsumsi Junk Food Terhadap Berat Badan - Wijaya, Nadya Videlia; Dahliah, Dahliah; Pancawati, Erni (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Fast food is food that can be prepared and served very quickly. Junk food refers to fast food that contains refined sugar, white flour, trans fat, salt, high unsaturated fat and many food additives such as monosodium glutamate (MSG) and tartrazine, as well as less protein, vitamins and fiber. This study used qualitative research methods. Data collection techniques are carried out by literature study. The data that has been collected is then analyzed through three stages, namely data reduction, data presentation and conclusions. The results showed that junk food such as burgers, French fries, pizza, grilled or fried chicken and chips generally contain a lot of saturated fat. Consumption of junk food has several impacts on health, one of them can cause changes in body weight, namely obesity. Since the 21st century, obesity has been referred to as a global pandemic because its spread from teenagers to adults due to junk food has been proven. The affordability, taste, accessibility, and variety of junk food on the market are key factors contributing to the impact it has on health. Keywords: Fast Food, Junk Food, Body Weight, Obesity  ABSTRAK Makanan cepat saji adalah makanan yang dapat disiapkan dan disajikan dengan sangat cepat. Junk food mengacu pada makanan cepat saji yang mengandung gula rafinasi, tepung putih, lemak trans, garam, lemak tak jenuh yang tinggi dan banyak bahan tambahan makanan seperti monosodium glutamat (MSG) dan tartrazine, serta kurang protein, vitamin dan serat. Junk food seperti burger, kentang goreng, pizza, ayam bakar atau goreng dan keripik umumnya mengandung banyak lemak jenuh. Konsumsi junk food memiliki beberapa dampak terhadap kesehatan yang diantaranya dapat menyebabkan kelebihan berat badan atau obesitas. Sejak abad ke-21, obesitas telah disebut sebagai pandemik global karena penyebarannya dari remaja ke orang dewasa yang terbukti mengonsumsi junk food. Keterjangkauan, rasa, aksesibilitas, dan variasi junk food di pasaran adalah faktor kunci yang berkontribusi terhadap dampak yang terjadi pada Kesehatan. Kata Kunci: Makanan Cepat Saji, Junk Food, Berat Badan, Obesitas